2017
DOI: 10.1039/c6tc04965f
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanodisc arrays as near infrared metal-enhanced fluorescence platforms with tuneable enhancement factors

Abstract: Au nanodisc arrays with nanoscale control of their structural characteristics, allow significant NIR fluorescence enhancement with tunable sensitivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 42 publications
(70 reference statements)
1
43
1
Order By: Relevance
“…Interestingly, instead of complete overlap, it has been shown that enhanced fluorescence occurs when the fluorophore emission peaks at a slightly longer wavelength than the LSPR peak. 23,24 In the past decade, there have been plentiful novel nanoparticle structures showing an ability to improve both the fluorescence intensity and the photostability of fluorophores via this mechanism, including nanorods, 25 nanocubes, 26 nanodisks, 27 nanotriangles 28 and nanostars 29 (Fig. 3A 30 ).…”
Section: General Criteria For a Mef Based Biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, instead of complete overlap, it has been shown that enhanced fluorescence occurs when the fluorophore emission peaks at a slightly longer wavelength than the LSPR peak. 23,24 In the past decade, there have been plentiful novel nanoparticle structures showing an ability to improve both the fluorescence intensity and the photostability of fluorophores via this mechanism, including nanorods, 25 nanocubes, 26 nanodisks, 27 nanotriangles 28 and nanostars 29 (Fig. 3A 30 ).…”
Section: General Criteria For a Mef Based Biosensormentioning
confidence: 99%
“…114 The variability of structures that can be produced is still expanding and ranges from rod arrays to rings, discs and crescents. 27,[115][116][117] In 2016, the amplification of light in NIR-II from Ag 2 S quantum dots was reported for the first time, achieving an enhancement of over 100 times when conjugated to nanotriangular arrays as produced via colloidal lithography. 67 Most notably, in 2017, protein microarrays based on NIR plasmonic gold nanostructures were reported for the highly sensitive detection of the pancreatic biomarker CA19-9.…”
Section: Towards Nir I and Nir Ii Biosensingmentioning
confidence: 99%
“…This leads to larger field enhancement at the LSPR, leading to a larger excitation enhancement in MEF. The LSPR is dependent not just upon material but also on the shape of the nanoparticle, and MEF has been successfully demonstrated in the NIR using triangular-like Ag nanoparticles immobilized on glass substrate [26,27], nanocylinders [22], and Nanostar [23]. Table 1 summarizes some of the results presented in published work by the Xie group at Imperial College for MEF in the NIR, for both Au and Ag nanoparticles, for excitation wavelengths up to 780 nm.…”
Section: Of 13mentioning
confidence: 97%
“…A higher carrier (doping) density is obtainable using ion implantation and annealing. Prucnal et al [22] achieved carrier concentrations of ~2.2 × 10 20 using rear side flash-lamp annealing (r-FLA). This gave n-Ge films of thickness 140 nm.…”
Section: Considering the Extinction Peaks Inmentioning
confidence: 99%
See 1 more Smart Citation